RE-DESAIN BUKU PANDUAN PRAMUKA UNTUK ANAK SEKOLAH DASAR - M. ZIKRI HANIF, Hendra Afriwan, S.Sn., M.Sn., Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Scouting is essentially an educational activity carried out outside the school campus and family  education environment under the responsibility of adult members, with the principle of scouting, an  important aim in education that is fun for young people with values based on Satya and Darma  Pramuka.The Book of Scout Guides for Elementary School is designed as a design solution for students who are  doing scouting activities. This book is re-designed using illustrations, text, colors, and attractive layouts  to suit the characteristics of children. The data analysis in the design of Scout Guidebook for Elementary School was carried out by SWOT analysis through data collected and observations to the  Quartir of the West Sumatra Regional Scout Movement, Padang State University Scout Activity Unit, and several Pandega, Trustees.The purpose of the re-design of this scout guide book was to produce a scout guide book for  elementary school children and presented in an interesting and communicative manner with  illustrations of different Indonesian scout characters with other scout book illustrations, as well as  information about personality education, personality formation activities, skills, and noble character of  scouts. The presentation of information on scout guide books for elementary school children with this  design is expected to increase the knowledge of scout alert students and provide benefits in scouting  activities.In addition to the Re-design of the Book of Scout Guides for Primary School, supported by several  media as the main media, this design includes other posters, x-banners, stickers, pencil boxes, drinking  bottles, and food boxes as supporting media books and as promotional media.Keywords: Re-design Scout Handbook, For Elementary School, Illustration